Gut Microbiota of Young Children Living in Four Brazilian Cities - Chew, Charmaine; Barros, Karina Vieira; Weffort, Virginia Resende Silva; Maranhão, Hélcio de Sousa; Laranjeira, Marisa; Knol, Jan; Roeselers, Guus; de Morais, Mauro Batista (Frontiers in Pediatrics, 2020)
Recent studies have demonstrated that gut microbiota development is influenced by human biogeographic factors such as race, ethnicity, diet, lifestyle or culture-specific variations, and other environmental influences. However, biogeographic variation in gut microbiota assembly remains largely unexplored in Latin America. In this paper, we compared food recall information and microbiota composition of toddlers living in geographically separated urban populations within four states of Brazil. 16S RNA gene sequencing revealed that alpha diversity was similar between the four different populations. Gut microbiota compositions were dominated by members of the phyla Firmicutes and Bacteroidetes, resembling a more adult-like microbiota as compared with those of Western European toddlers of similar age. These findings suggest that inter-individual and nutrition-induced differences were apparent in the fecal microbiota. We conclude that urban dietary pattern plays a larger role in influencing the gut microbiota composition than do biogeographic factors.